Analisis Strategi Penyelesaian Pembiayaan Bermasalah Pada Produk Murabahah Dalam Perspektif Ekonomi Syariah (Studi Kasus Pada Ksu Karya Terpadu Syariah Rarang Tahun 2020-2023 - Utomo, Danang Prio; Riswanto, Agus; Marlina, Marlina (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2024)
This study aims to: 1) identify the factors causing problematic financing in murabahah products at KSU Karya Terpadu Syariah Rarang, 2) determine the strategies for resolving problematic financing in murabahah products at KSU Karya Terpadu Syariah Rarang, and 3) analyze the strategies for resolving problematic financing in murabahah products from the perspective of Islamic economics at KSU Karya Terpadu Syariah Rarang.This research used a qualitative approach with a case study design. The data used included both primary and secondary data. Data collection techniques in this study involved observation, interviews, and documentation. The data analysis procedure used qualitative data analysis techniques.The results of this study indicate that: 1) the factors causing problematic financing in murabahah products stem from two sources: internal and external factors. 2) The strategies for resolving problematic financing in murabahah products at KSU Karya Terpadu Syariah Rarang include maintaining communication with customers, rescheduling, reconditioning, and confiscating and selling collateral. 3) Based on the analysis, the strategies for resolving problematic financing in murabahah products at KSU Karya Terpadu Syariah Rarang are in accordance with the perspective of Islamic economics, DSN MUI fatwas on murabahah financing, and do not contradict sharia principles